Kinetic isotope effects on the dissolution kinetics of solid salicylic acid in aqueous solution: Evidence for solubilisation via a proton dissociation-recombination mechanism - Wilkins, S; Coles, B; Compton, R (2002)
Quantitative Atomic Force Microscopy measurements made on the dissolving surface of solid salicylic acid in H2O and D2O reveal a kinetic isotope effect (kH/kD = 2.3 ± 0.6) on the dissolution rate consistent with a transition state in which the proton is dissociated from the dissolving molecule.